Studying Implicit Attitudes Towards Smoking: Event-Related Potentials in the Go/NoGo Association Task - Wagner-Altendorf, Tobias A.; van der Lugt, Arie H.; Banfield, Jane F.; Deibel, Jacqueline; Cirkel, Anna; Heldmann, Marcus; Münte, Thomas F. (Frontiers in Human Neuroscience, 2021)
Cigarette smoking and other addictive behaviors are among the main preventable risk factors for several severe and potentially fatal diseases. It has been argued that addictive behavior is controlled by an automatic-implicit cognitive system and by a reflective-explicit cognitive system, which operate in parallel to jointly drive human behavior. The present study addresses the formation of implicit attitudes towards smoking in both smokers and non-smokers, using a Go/NoGo association task (GNAT), and behavioral and electroencephalographic measures. The GNAT assesses, via quantifying participants’ reaction times, the strength of association between a target category and either pole of an evaluative dimension (positive or negative). EEG analysis is performed to determine the temporal course of the event-related potential (ERP) components underlying Go/NoGo decisions and implicit attitude formation. Both smokers and non-smokers showed prolonged reaction times to smoking-related pictures when the pictures were coupled with positive evaluative words (“incongruent condition”). This indicates negative implicit attitudes towards smoking in both groups alike at the time point of the behavioral response (600-700 ms post stimulus). However, only the non-smokers, not the smokers, were found to show a delay of the N200 component in the incongruent condition. This is interpreted as reflecting ambivalent or even positive implicit attitudes towards smoking in the smoker group at the time point of the N200 (300-400 ms post stimulus). Our study thus provides evidence for the hypothesis that implicit attitudes are subject to changes within several hundred milliseconds after stimulus presentation, and can be altered in the course of their formation.